The Correlation between Dietary Compliance and Random Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Anita Dahliana; Agnes Mirandadea Evangelista Manek; Puri Safitri Hanum; Winnie Nirmala Santosa (Postgraduate, University of Mataram, 2025)
Diabetes mellitus is a chronic disease that is a major problem of morbidity and mortality worldwide. Type 2 diabetes mellitus is caused by several factors, one of which is dietary compliance, which is key to the management of type 2 diabetes mellitus and long-term glycemic control. Research Objective to determine whether or not there is a relationship between the level of dietary compliance with the level of random blood sugar levels of patients with type 2 diabetes mellitus. Methods: A quantitative research type with a cross-sectional approach method with a total of 50 respondents. Results: Based on the results of statistical tests using Spearman Rho with α = 0.05 (5%) between the level of dietary compliance with random blood sugar levels of patients with type 2 diabetes mellitus in May 2024 showed a significant value of ρ = 0.008 (ρ-value <0.05) and the direction of the strength of the relationship with a value of r = -0.369 which means it shows the variable is sufficient correlated. Conclusion: There is a significant relationship between the level of dietary compliance and random blood sugar levels in patients with type 2 diabetes mellitus.